2020
DOI: 10.21470/1678-9741-2019-0240
|View full text |Cite
|
Sign up to set email alerts
|

Transcaval Access to the Abdominal Aorta: indications of Interest to Surgeons and a Comprehensive Literature Review

Abstract: We performed a review of the literature (until August 01, 2019) on the occasion of the first transcaval approach for transcatheter aortic valve implantation in our hospital. This review focuses mainly on the indications of this alternative access route to the aorta. It may be useful for vascular surgeons in selected cases, such as the treatment of endoleaks after endovascular aneurysm repair and thoracic endovascular aneurysm repair. We describe historical aspects of transcaval access to the aorta, experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Historically, the first application of transcaval access to the aorta was done in the management of type 2 endoleak by Mansueto et al 4 However, the bulk of research on the transcaval was spearheaded by Robert Lederman and Adam Greenbaum, who focused on this approach as an alternative to transfemoral access for transcatheter aortic valve repair (TAVR). 5 In 2013, Halabi et al, which included Lederman, published a preclinical study performing transcaval access to aorta in 14 swine with successfully fistula occlusion and survival in all 14 specimens. They listed several potential benefits to this approach such as a more compliant venous conduit, non-life-threatening fistula, and reduction of hemorrhage risk due to the IVC's ability to decompress arterial ruptures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the first application of transcaval access to the aorta was done in the management of type 2 endoleak by Mansueto et al 4 However, the bulk of research on the transcaval was spearheaded by Robert Lederman and Adam Greenbaum, who focused on this approach as an alternative to transfemoral access for transcatheter aortic valve repair (TAVR). 5 In 2013, Halabi et al, which included Lederman, published a preclinical study performing transcaval access to aorta in 14 swine with successfully fistula occlusion and survival in all 14 specimens. They listed several potential benefits to this approach such as a more compliant venous conduit, non-life-threatening fistula, and reduction of hemorrhage risk due to the IVC's ability to decompress arterial ruptures.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, there has been significant interest in the evaluation of transcaval embolization as a strategy for the treatment of endoleaks in patients with complicated anatomic features. Sánchez et al 5 reviewed seven studies with a total of 93 patients undergoing transcaval embolization for type 2 endoleaks. They found that all of these studies had favorable outcomes with success rates between 90 and 100%.…”
Section: Discussionmentioning
confidence: 99%